Who coined the term “One Health”? Cooperation amid the siloization - Christina Pettan-Brewer; Gillian Penn; Alexander W. Biondo; Thomas Jaenisch; Kim Grützmacher; Laura H. Kahn (One Health, 2024)
This short communication is an effort to describe and elucidate the trajectory of the modern historical concept of “One Health.” It is dedicated to the many integrated approaches of health closely related to One Health, while also recognizing the contribution and origination of One Health perspectives/notions from those that have led the way and spearheaded this movement while considering Indigenous cultures across the world. The effects of synergies of those involved in building these integrative approaches are potentially bigger and better lasting than the sum of the individual players. It is only through collaboration, cooperation and diplomacy that we can achieve impactful transformation to benefit health. In this commentary, we aim to appropriately and accurately describe how the current use of “One Health” came to be and who were the main players.